Factors Influencing Saccadic Reaction Time: Effect of Task Modality, Stimulus Saliency, Spatial Congruency of Stimuli, and Pupil Size - Yamagishi, Shimpei; Furukawa, Shigeto (Frontiers in Human Neuroscience, 2020)
It is often assumed that the reaction time of a saccade toward visual and/or auditory stimuli reflects the sensitivities of our oculomotor-orienting system to stimulus saliency. Endogenous factors, as well as stimulus-related factors, would also affect the saccadic reaction time (SRT). However, it was not clear how these factors interact and to what extent visual and auditory-targeting saccades are accounted for by common mechanisms. The present study examined the effect of, and the interaction between, stimulus saliency and audiovisual spatial congruency on the SRT for visual- and for auditory-target conditions. We also analyzed pre-target pupil size to examine the relationship between saccade preparation and pupil size. Pupil size is considered to reflect arousal states coupling with locus-coeruleus (LC) activity during a cognitive task. The main findings were that (1) the pattern of the examined effects on the SRT varied between visual- and auditory-auditory target conditions, (2) the effect of stimulus saliency was significant for the visual-target condition, but not significant for the auditory-target condition, (3) Pupil velocity, not absolute pupil size, was sensitive to task set (i.e., visual-targeting saccade vs. auditory-targeting saccade), and (4) there was a significant correlation between the pre-saccade absolute pupil size and the SRTs for the visual-target condition but not for the auditory-target condition. The discrepancy between target modalities for the effect of pupil velocity and between the absolute pupil size and pupil velocity for the correlation with SRT may imply that the pupil effect for the visual-target condition was caused by a modality-specific link between pupil size modulation and the SC rather than by the LC-NE (locus coeruleus-norepinephrine) system. These results support the idea that different threshold mechanisms in the SC may be involved in the initiation of saccades toward visual and auditory targets.